A bottom-up route to enhance thermoelectric figures of merit in graphene nanoribbons - Sevincli, Haldun; Sevik, Cem; Cagin, Tahir; Cuniberti, Gianaurelio (Giovanni) (Scientific Reports, 2013)
We propose a hybrid nano-structuring scheme for tailoring thermal and thermoelectric transport properties of graphene nanoribbons. Geometrical structuring and isotope cluster engineering are the elements that constitute the proposed scheme. Using first-principles based force constants and Hamiltonians, we show that the thermal conductance of graphene nanoribbons can be reduced by 98.8% at room temperature and the thermoelectric figure of merit, ZT, can be as high as 3.25 at T = 800â ..K. The proposed scheme relies on a recently developed bottom-up fabrication method, which is proven to be feasible for synthesizing graphene nanoribbons with an atomic precision.
CRIS-Team Scopus Importer:2023-03-20